2019
DOI: 10.1017/cem.2019.432
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between triage acuity and frailty to inform the care of older emergency department patients: Findings from a large Canadian multisite cohort study

Abstract: BackgroundThe 2016 Canadian Triage and Acuity Scale (CTAS) updates introduced frailty screening within triage to more accurately code frail patients who may deteriorate waiting for care. The relationship between triage acuity and frailty is not well understood, but may help inform which supplemental geriatric assessments are beneficial to support care in the emergency department (ED). Our objectives were to investigate the relationship between triage acuity and frailty, and to compare their associations with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…We used the Canadian Triage and Acuity Scale (CTAS) to assess illness acuity [ 7 , 20 ]. The CTAS is a descriptive 5-point triage scale, where level 1 is resuscitation, 2 is emergent, 3 is urgent, 4 is less urgent and 5 is non-urgent.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the Canadian Triage and Acuity Scale (CTAS) to assess illness acuity [ 7 , 20 ]. The CTAS is a descriptive 5-point triage scale, where level 1 is resuscitation, 2 is emergent, 3 is urgent, 4 is less urgent and 5 is non-urgent.…”
Section: Methodsmentioning
confidence: 99%
“…It is strongly associated with increased risks of death and of worsening health status, notably among older patients with acute medical conditions [ 3–7 ]. This relationship is less studied among patients in the emergency department (ED) setting [ 7–10 ], despite its implications for appropriate care planning [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 However, prior work has demonstrated that in geriatric populations, frailty and geriatric complexity are what drive health service use and clinical outcomes, rather than patient age. 22,[46][47][48] Though prior reviews report age as an important pre-arrest prognostic factor, we hypothesize that this relationship is likely confounded by frailty. Similarly, older patients without signi cant frailty may be at lower risk of morbidity and mortality than those with frailty, and therefore CPR may provide a greater bene t in this population.…”
Section: Discussionmentioning
confidence: 96%
“…Neither of these instruments performed well enough to be used as the sole screening tool (7,8). The Canadian ED frailty index tool seemed to predict adverse outcomes in individual studies (9,10).…”
Section: In the Past Other Tools Such As The Identi Cation Of Seniormentioning
confidence: 99%